nm23-H1基因转染前后人高转移大细胞肺癌细胞株的比较蛋白质组学研究 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: As a tumor metastasis suppressor gene, the functions of nm23-H1 gene are still unclear. The aim of this study is to better understand the mechanism of lung cancer metastasis and to find new biomarkers for early diagnosis and new target for therapy by conducting comparative proteomics between the human high-metastatic large cell lung cancer cell lines (L9981) and L9981-nm23-H1 (constructed with transfecting nm23-H1 gene into the L9981 cell line). METHODS: The total proteins of L9981 and L9981-nm23-H1 were separated by immobilized pH gradient (IPG)-based 2-dimensional electrophoresis (2-DE); the significantly differently expressed proteins were examined by mass spectrometry and analyzed by bioinformatics. RESULTS: It was observed that nm23-H1 gene transfection caused remarkable changes of the proteome of L9981 compared with L9981-nm23-H1 cells: 5 proteins were deleted, 9 proteins appeared, 16 proteins downregulated, and 12 proteins up-regulated. These proteins are involved in cell framework, signal transduction, metabolism, proliferation and metastasis. CONCLUSION: After nm23-H1 gene is transfected into L9981, proteome in L9981 is remarkably changed. These changes of the proteome could serve as a basis for reversing the invasive and metastatic phenotype in lung cancer and elucidating the machanisms of the metastasis of lung cancer.